Quantitative real time PCR for distinction between Pneumocystis jirovecii infection/colonization in hospitalized patients - Rouhi, Faezeh; Erami, Mahzad; Rastgufar, Sepide; Jahani, Maryam; Aboutalebian, Shima; Soltani, Sajedeh; Fakhim, Hamed; Mirhendi, Hossein (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundIdentification of the opportunistic fungus Pneumocystis jirovecii in respiratory specimens presents challenges, particularly in differentiating between colonization and active infection. The present study assessed a probe-based real time PCR (qPCR) diagnostic effectiveness in patients with diverse underlying conditions, particularly those with COVID-19 and pulmonary insufficiency.MethodsTo set up the qPCR, clinical samples from 281 patients with respiratory ailments were tested. Subsequently, a descriptive study was conducted on 112 patients with pulmonary insufficiency with and without COVID-19 suspected of P. jirovecii infection. All specimens were subjected to DNA extraction followed by nested PCR and qPCR targeting the mitochondrial large subunit (mtLSU)-rRNA gene.ResultsBased on nested PCR and qPCR, P. jirovecii was identified in 40 out of 281 patients, with slight variations in positive samples observed across dilutions. Three patients who tested positive in nested PCR yielded negative results in probe-based qPCR. Conversely, three patients who tested positive in probe-based qPCR yielded negative results in nested PCR. Considering nested PCR as the golden standard, probe-based qPCR demonstrated good diagnostic performance, with 92.5% sensitivity and 98.7% specificity. Based on cycle threshold (Ct) values, the positive cases were categorized: ≤32 as infection, >35 as colonization, and a grey zone between these values (32 < X ≤ 35). The analysis of 112 PCP-suspected patients revealed a prevalence ranging from 6.25% (nested PCR) to 7% (probe-based qPCR).ConclusionsThis study suggested Ct values to differentiate Pneumocystis pneumonia/colonization in immunocompromised patients. To further augment the diagnostic sensitivity, it is recommended to integrate qPCR results with clinical parameters and biomarkers to offer a more precise understanding of Pneumocystis-related conditions.